Population Fluctuations and Abundance Indices of Mosquitoes (Diptera: Culicid), as the Potential Bridge Vectors of Pathogens to Humans and Animals in Mazandaran Province, Northern Iran - Seyed Hassan Nikookar; Mahmoud Fazeli-Dinan; Ahmadali Enayati (Tehran University of Medical Sciences, 2022)
Background: Seasonal activity patterns of mosquitoes are essential as baseline knowledge to understand the transmission dynamics of vector-borne diseases. This study was conducted to evaluate the monthly dynamics of the mosquito populations and their relation to meteorological factors in Mazandaran Province, north of Iran. Methods: Mosquito adults and larvae were collected from 16 counties of Mazandaran Province using different sampling techniques, once a month from May to December 2014. "Index of Species Abundance" (ISA) along with "Standardized ISA" (SISA) was used for assessing the most abundant species of mosquitoes based on the explanations of Robert and Hsi. Pearson's correlation coefficient (R) was used to assess the relationships between the monthly population fluctuations and meteorological variables. Results: Overall, 23750 mosquitoes belonging to four genera and nineteen species were collected and identified. The highest population density of mosquitoes was in July and the lowest in May. The ISA/SISA indices for Culex pipiens were both 1 for larvae and 1.25/0.973 for adults in total catch performed in human dwellings. For Cx. tritaeniorhynchus, the ISA/SISA were 1.68/0.938 in pit shelter method. A significant positive correlation was observed between population fluctuations of Cx. tritaeniorhynchus and mean temperature (R: 0.766, P< 0.027). Conclusions: The results indicated that the mosquitoes are more active in July, and Cx. pipiens and Cx. tritaeniorhynchus were the most abundant species. Considering the potential of these species as vectors of numerous pathogens, control programs can be planed based on their monthly activity pattern in the area.